Simulation of combined body tilt system of high-speed railway rolling stock - Yeritsyan, Bagish; Liubarskyi, Borys; Iakunin, Dmytro (Eastern-European Journal of Enterprise Technologies, 2016)
The actual problem of creating a high-speed railway rolling stock with a combined electromechanical and pneumatic body tilt system is considered. Using the proposed simulation model created in the MATLAB environment, simulation of the rolling stock body tilt while passing a curved track section is carried out. To determine the parameters of the elements of electromechanical and pneumatic drive units, information is necessary about the electrophysical processes, occurring in the tilt system and determining the input parameters for the design of the considered tilt system. The dynamic performance of components of the proposed mechanism is identified, which allows giving practical advice on the choice of parameters of semiconductor converter elements, pneumatic and electromechanical devices of the combined tilt system, and also determining the forces acting in the tilt mechanism elements. Based on these dependencies, it is possible to choose the element base of the semiconductor converter (types of keys and diodes), parameters and types of cylinders of air springs, as well as to determine the load of the elements of the overbogie structure of the rolling stock. The results can be used in the development and design of high-speed railway rolling stock without substantial reconstruction of the existing transport infrastructure.